History of suicide attempts in pediatric bipolar disorder: factors associated with increased risk - Goldstein, Tina R (2005)
BACKGROUND: Despite evidence indicating high morbidity associated with pediatric bipolar disorder (BP), little is known about the prevalence and clinical correlates of suicidal behavior among this population. OBJECTIVE: To investigate the prevalence of suicidal behavior among children and adolescents with BP, and to compare subjects with a history of suicide attempt to those without on demographic, clinical, and familial risk factors. METHODS: Subjects were 405 children and adolescents aged 7–17 years, who fulfilled DSM-IV criteria for BPI (n = 236) or BPII (n = 29), or operationalized criteria for BP not otherwise specified (BP NOS; n = 140) via the Schedule for Affective Disorders and Schizophrenia for School-Aged Children. As part of a multi-site longitudinal study of pediatric BP (Course and Outcome of Bipolar Youth), demographic, clinical, and family history variables were measured at intake via clinical interview with the subject and a parent/guardian. RESULTS: Nearly one-third of BP patients had a lifetime history of suicide attempt. Attempters, compared with non-attempters, were older, and more likely to have a lifetime history of mixed episodes, psychotic features, and BPI. Attempters were more likely to have a lifetime history of comorbid substance use disorder, panic disorder, non-suicidal self-injurious behavior, family history of suicide attempt, history of hospitalization, and history of physical and/or sexual abuse. Multivariate analysis found that the following were the most robust set of predictors for suicide attempt: mixed episodes, psychosis, hospitalization, self-injurious behavior, panic disorder, and substance use disorder. CONCLUSIONS: These findings indicate that children and adolescents with BP exhibit high rates of suicidal behavior, with more severe features of BP illness and comorbidity increasing the risk for suicide attempt. Multiple clinical factors emerged distinguishing suicide attempters from non-attempters. These clinical factors should be considered in both assessment and treatment of pediatric BP.